2003
DOI: 10.1074/jbc.m208033200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Excystation of the Early Diverging Eukaryote, Giardia lamblia

Abstract: Excystation of Giardia lamblia, which initiates infection, is a poorly understood but dramatic differentiation induced by physiological signals from the host. Our data implicate a central role for calcium homeostasis in excystation. Agents that alter cytosolic Ca 2؉ levels (1,2-bis(2-aminophenoxy)ethane-N,N,N ,N -tetraacetic acidtetra(acetyloxymethyl) ester, a Ca 2؉ channel blocker, Ca 2؉ ionophores, and thapsigargin) strongly inhibit excystation. Treatment of Giardia with thapsigargin raised intracellular Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
(79 reference statements)
4
18
0
Order By: Relevance
“…In Giardia trophozoites, gPP2A-C localizes to the eight basal bodies, as previously reported for giardial PKAc/r, the MAP kinase ERK1, centrin, and calmodulin [7][8][9]24,38,39]. gPP2A-C also localizes to the ventral disk (similar to ERK 1 [9]), to the anterior and caudal PDR (similar to PKAc/r [7,8]) and to the posterior-lateral PDR (similar to centrin [24]).…”
Section: Discussionsupporting
confidence: 81%
“…In Giardia trophozoites, gPP2A-C localizes to the eight basal bodies, as previously reported for giardial PKAc/r, the MAP kinase ERK1, centrin, and calmodulin [7][8][9]24,38,39]. gPP2A-C also localizes to the ventral disk (similar to ERK 1 [9]), to the anterior and caudal PDR (similar to PKAc/r [7,8]) and to the posterior-lateral PDR (similar to centrin [24]).…”
Section: Discussionsupporting
confidence: 81%
“…Bernal et al (1998) evaluated the effect of CaM inhibitors and found that excystation (shift from cyst to trophozoite) decreased in the presence of TFP and W-7 compounds. Reiner et al (2003) repeated these inhibition experiments and confirmed that CaM was involved in parasite excystation. They also sequenced the CaM gene and found, by analyzing the translated sequence, that the protein was divergent and differed from the consensus of all available sequences in ten positions (Reiner et al 2003).…”
Section: Introductionsupporting
confidence: 70%
“…Reiner et al (2003) repeated these inhibition experiments and confirmed that CaM was involved in parasite excystation. They also sequenced the CaM gene and found, by analyzing the translated sequence, that the protein was divergent and differed from the consensus of all available sequences in ten positions (Reiner et al 2003). This is very interesting because CaM has been one of the most conserved proteins during evolution (Stathopulos et al 2007).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Once ingested, the cyst becomes metabolically active, and excystation occurs within as little as 15 min (52). Excystation is dependent upon the gastric acid of the host stomach, cysteine proteases produced by G. duodenalis peripheral vesicles, the phosphorylation/dephosphorylation of cyst wall proteins, and Ca 2ϩ signaling (52)(53)(54)(55). The released excyzoite undergoes two rounds of binary fission while upregulating processes related to mobility and the organization of the adhesive disc (56).…”
Section: Giardiasis Life Cycle and Mechanisms Of Virulencementioning
confidence: 99%